Pengaruh Komponen Good Corporate Governance Pada Nilai Perusahaan: Studi Empiris Pada Perusahaan Terindeks Sri-Kehati - Elsa Isabel; Ni Made Dwi Ratnadi (Serat Acitya, 2023)
Good corporate governance appears to control behavior and resolve conflicts between parties within the company. This study aims to determine the effect of good corporate governance components on firm value. This study examines 88 companies listed twice a year in the SRI-KEHATI Index in 2019-2022. The components of good corporate governance in this study are proxied by managerial ownership, institutional ownership, independent commissioner composition, and board size. This study uses firm size as a control variable. The analysis technique used is multiple linear regression analysis. The results of the analysis show that managerial ownership, institutional ownership, and board size have a positive and insignificant effect (95 percent confidence level) on firm value while the composition of independent commissioners has a significant positive effect on firm value. The implication of this research is that companies with a high composition of independent commissioners indicate that independent commissioners supervise and coordinate well in maintaining a balance between the interests of majority and minority shareholders so that it has an impact on increasing firm value.